Utilization of Mixture of Teak Wood Sawdust and Bagasse Fiber using Treatment of Fiber Variations and Alkali NaOH Immersion as A Refrigerator Insulation Material - Alam Baheramsyah; Ede Mehta Wardhana; Achmad Taufik Rendi Kisserah (Institut Teknologi Sepuluh Nopember, 2019)
This research modified the insulation of coolbox material by utilizing a mixture of teak wood sawdust (Tectona grandis L.f.) and previously immersed bagasse fiber (Saccharum officinarum) into an alkali NaOH solution to improve the mechanical properties of the fiber and reduce the value of material thermal conductivity. The most optimal test and analysis results were obtained by composing 50% teak wood sawdust with 50% of previously immersed bagasse fiber in an alkali NaOH solution at a level of 15%. The obtained conductivity value is 0.2907 W / mK, the density is 0.4901 gram / cm3. Experiments on changes in temperature of ice, fish, and coolbox chamber as well as experiments on the duration of fish preservation in the coolbox with variations in the composition of straight fibers have better performance compared to the variation of random fiber which is able to preserve fish for 34 hours with minimum temperature of 0, 2 ° C. For fishing duration of two days, coolbox with a variety of straight fiber has almost the same performance as coolbox made from styrofoam and has the potential to replace styrofoam because it is more environmentally friendly.